Impact of insect pollinators on yields of Glycine max L. (Fabaceae) at Yaoundé (Cameroon) Douniaa, Clautin Ningatoloumb, Chantal Doukaa, Elono Azang Pierre Stephana, Amada Brahimc, Joseph Lebel Tamessea, Fernand-Nestor Tchuenguem Fohouod - Dounia; Clautin Ningatoloum; Chantal Doukaa; Elono Azang Pierre Stephan; Amada Brahim; Joseph Lebel Tamesse; Fernand-Nestor Tchuenguem Fohouo (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
To appreciate the impact of insect pollinators on the pod, seeds, and seed weight yields of Glycine max, the pollinating activities of flowering insects were studied in Yaoundé, during the two mild, rainy seasons in 2016 and 2017 (March-June). Observations were made on 45 to 20400 flowers per treatment. The flowers were subjected to different treatments: Free flowers (Treatment 1), bagged flowers (treatment 2), castrated and free flowers (treatment 3), and castrated and bagged flowers (treatment 4). Some (8695 and 3325) flowers of Glycine max (Fabaceae) were observed in 2016 and 2017, respectively, for the diversity and Frequency of insect visits. For results, 1527 visits of 13 insect species distributed in seven orders were recorded on G. max flowers. The most dominating Hymenoptera observed was Apis mellifera, with 40.20 % of the total insect visits. The highest number of insect pollinators harvested in the flowers of this Fabaceae was between 8h-9h. The studied insects have a positive impact on the yields of this plant. This positive impact of the pollinator insects on the yields was 26.29 %, 16.13 %, 15.02 and 4.45 % in fructification rate, number of seeds pod, the weight of seeds, and percentage of normal seeds respectively. The avoidance of pesticide treatment of plants during flowering could be a good management strategy to improve on plant yield.